STRATEGI KREATIF IKLAN LAYANAN MASYARAKAT (ILM) DALAM PEMASARAN SOSIAL - Naima Khoiru Nisa (Interaksi: Jurnal Ilmu Komunikasi, 2015)
Abstract:Public Service Announcements (PSAs) is one form of promotion strategies are often used insocial marketing activities. Like commercials in general, PSAs should have an effective message tobe able to change the behavior of the target adopter as desired social marketers. So it takes a creativestrategy in the preparation of a persuasive message and also the media placement of the PSAs thatthe ad is more effective in inducing the target adopter to change behavior.